1997
DOI: 10.1073/pnas.94.10.5067
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Bcl-xLexpression in human keratinocytes by cell–substratum adhesion and the epidermal growth factor receptor

Abstract: Cell-substratum adhesion is an essential requirement for survival of human neonatal keratinocytes in vitro. Similarly, activation of the epidermal growth factor receptor (EGF-R) has recently been implicated not only in cell cycle progression but also in survival of normal keratinocytes. The mechanisms by which either cell-substratum adhesion or EGF-R activation protect keratinocytes from programmed cell death are poorly understood. Here we describe that blockade of the EGF-R and inhibition of substratum adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
80
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 50 publications
(32 reference statements)
5
80
0
2
Order By: Relevance
“…Heparin-binding EGF-like growth factor (HB-EGF) is included in Figure 3a (Nass et al, 1996). Moreover, Rodeck and colleagues have recently reported results similar to our own in keratinocytes (Rodeck et al, 1997a). Our studies are the ®rst to demonstrate a functional role for Bcl-X L in EGFR-dependent KC survival.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Heparin-binding EGF-like growth factor (HB-EGF) is included in Figure 3a (Nass et al, 1996). Moreover, Rodeck and colleagues have recently reported results similar to our own in keratinocytes (Rodeck et al, 1997a). Our studies are the ®rst to demonstrate a functional role for Bcl-X L in EGFR-dependent KC survival.…”
supporting
confidence: 79%
“…However, we found that protection from PD153035-induced apoptosis was never complete (Figure 4). Rodeck and colleagues reported a similar result, in that keratinocyte apoptosis developed only gradually after mAb-mediated blockade of ErbB-1 signaling, becoming detectable only after 4 to 5 days of mAb treatment (Rodeck et al, 1997b). These ®ndings suggest at least three possibilities: (i) that loss of ErbB signaling triggers multiple downstream cell death pathways, only some of which can be blocked by Bcl-X L ; (ii) that Bcl-X L exerts only a modulatory or stochastic e ect on a ®nal common pathway of cell death, rather than an all-or-nothing e ect; or (iii) that the ErbB pathway interacts with other signaling systems to maintain cell survival.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Bcl-X L levels returned to baseline 72 h following irradiation in U87/SIRPa1 cells, while cells expressing vector without insert showed sustained elevation in bcl-X L protein levels 24 ± 72 h following g-irradiation ( Figure 3d). Modulation of Bcl-X L protein levels has also been shown to in¯uence sensitivity to apoptosis in EGFR-containing keratinocytes exposed to cell death signals (Rodeck et al, 1997).…”
Section: Sirpa1 Modulation Of Egfr-mediated Cell Growth and Transformmentioning
confidence: 99%
“…Anoikis of various types of non-malignant epithelial cells such as those of intestine, skin and breast is executed by several, rather than one, proapoptotic mechanisms (Rodeck et al, 1997;Rytomaa et al, 1999;Gilmore et al, 2000;Rosen et al, 2000Rosen et al, , 2002Puthalakath et al, 2001;Reginato et al, 2003). The reasons why several death-promoting events are required for the induction of this form of apoptosis have not so far been identified.…”
Section: Discussionmentioning
confidence: 99%